Acceptance of E-learning among university students in UAE: A practical study - Ahmad Qasim Mohammad AlHamad (Institute of Advanced Engineering and Science, 2020)
The objective of the study is to find out the factors which affect the acceptance of E-learning among students and how the students’ purpose of using E-learning is determined by these factors. The research was based on the Technology Acceptance Model (TAM). The researcher developed a questionnaire to gather data from a sample of 366 university students who actively used the E-learning system. According to the results of the study, subjective norms, perceived usefulness, perceived ease of use, enjoyment, and accessibility” are the vital predictors behind the intention of students for using E-learning systems. This indicates that extended TAM is applicable in the UAE. The results show that policymakers and education developers should take E-learning system seriously since it can be opted not just as a technological solution but also as a learning platform for students belonging to a distant area. The results present practical implications for education developers, policymakers and practitioners in devising useful plans to implement E-learning systems.